2016
DOI: 10.1038/labinvest.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl isomerase Pin1 promotes survival in EGFR-mutant lung adenocarcinoma cells with an epithelial–mesenchymal transition phenotype

Abstract: The secondary epidermal growth factor receptor (EGFR) T790M mutation is the most prominent mechanism that confers resistance to first-or second-generation EGFR tyrosine kinase inhibitors (TKIs) in lung cancer treatment. Although third-generation EGFR TKIs can suppress the kinase activity of T790M-positive EGFR, they still cannot eradicate EGFR-mutated cancer cells. We previously reported that a subpopulation of EGFR-mutant lung adenocarcinomas depends on enhanced autophagy, instead of EGFR, for survival, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…We searched for other mechanism(s) that these EGFR ‐mutant cells devoid of EGFR dependency rely on, and found that the mesenchymal EGFR ‐mutant cells depend on enhanced autophagy for survival (Fig. c) . Although it has been reported that AXL kinase plays a key role in the survival of mesenchymal EGFR ‐mutant cells, we did not find evidence suggesting that such cells derived from HCC827 or HCC4006 cells are addicted to the kinase for survival …”
Section: Emt: An Egfr‐independent Mechanism Of Tki Resistancementioning
confidence: 78%
See 3 more Smart Citations
“…We searched for other mechanism(s) that these EGFR ‐mutant cells devoid of EGFR dependency rely on, and found that the mesenchymal EGFR ‐mutant cells depend on enhanced autophagy for survival (Fig. c) . Although it has been reported that AXL kinase plays a key role in the survival of mesenchymal EGFR ‐mutant cells, we did not find evidence suggesting that such cells derived from HCC827 or HCC4006 cells are addicted to the kinase for survival …”
Section: Emt: An Egfr‐independent Mechanism Of Tki Resistancementioning
confidence: 78%
“…In the three TKI‐resistant cells, E‐cadherin (a representative epithelial marker) and TTF‐1 were markedly reduced, while expression levels of vimentin, ZEB1 (an EMT‐inducing transcription factor), and CD44 standard form (CD44s) were elevated compared with the parental cells (Fig. b), indicating that they exhibited a mesenchymal phenotype and consequently lost features of alveolar epithelia . Considering that EGFR ‐mutant cells that have completed EMT readily emerge, and the parental cells contain a minor subpopulation (<2%) of cells that express CD44s, it is likely that TKI treatment selects for these mesenchymal cells among the parental cells .…”
Section: Emt: An Egfr‐independent Mechanism Of Tki Resistancementioning
confidence: 98%
See 2 more Smart Citations
“…Consistently, PIN1 silencing suppresses protein expression and promoter activity of EMT regulator SNAIL, leading to increased expression of its downstream effector E-cadherin in tamoxifen-resistant breast cancer cells[96]. In epidermal growth factor receptor (EGFR) Thr 790 Met mutant lung cancer tissues, PIN1 expression is also positively correlated with the mesenchymal markers vimentin and Zeb1[97]. PIN1 expression enhances the survival of EGFR-mutant lung adenocarcinoma cells with an EMT phenotype.…”
Section: Roles Of Pin1 In Tumour Invasivenessmentioning
confidence: 99%